Gestión administrativa-operativa de la unidad nacional de almacenamiento y su impacto en la rentabilidad de los productos de maíz, del cantón Quevedo, año 2012, Plan de comercialización. - Santana Alcívar, Félix Edmundo (2013)
This research was conducted in order to evaluate the impact of the Administrative - Operational National Storage Unit on the profitability of corn producers Quevedo Canton, because some of the problems identified: Administrative How -Operative Management the National Storage Unit Profitability impacts on corn Producers Quevedo Canton? The ONE is designed to support the productive critical of Quevedo Canton and surrounding areas depending on the requirements established , reason is to prove the following hypothesis : Administrative -Operative Management of the National Storage Unit generates low returns in the corn producers Quevedo canton . National Storage Unit is a public entity under the Ministry of Agriculture, Livestock, Aquaculture and Fisheries, with legal personality, its own, independent budget, administrative and financial autonomy, established in the city of Quito, whose purpose is help the producer. The general objective was raised in this research is to evaluate the impact of the administrative -operative National Storage Unit on the profitability of corn producers Quevedo Canton. To determine the impact of delayed marketing process A in the income of corn farmers Quevedo. Identify the impact of capacity levels of regulation and control of the UNA in the standardization and commercialization of prices Corn Establish the level of profitability of corn producers Quevedo Canton and its relation to the sale of the product to the AN ......................................................................